Characterization of Crustal and Uppermost‐Mantle Seismic Discontinuities in the Ontong Java Plateau. Issue 7 (30th July 2019) - Tonegawa, T.; Miura, S.; Ishikawa, A.; Sano, T.; Suetsugu, D.; Isse, T.; Shiobara, H.; Sugioka, H.; Ito, A.; Ishihara, Y.; Tanaka, S.; Obayashi, M.; et al.
Abstract: The Early Cretaceous Ontong Java Plateau (OJP) in the southwestern Pacific Ocean is the largest oceanic plateau by volume on Earth, and a broad range of observations has been conducted to reveal its formation and evolution. However, because seafloor seismic observations of the OJP and surrounding areas have been insufficient so far, such experiments are capable of generating additional information regarding the crustal and mantle structure of the OJP. To image seismic velocity discontinuities from the crust to the uppermost mantle, we applied receiver function analysis to seismic records acquired by 17 broadband ocean bottom seismometers deployed across the region in and around the OJP and 3 broadband stations located on ocean islands in Micronesia (one: permanent, two: temporary). The results revealed midcrustal discontinuities and the Moho at depths of 10–20 and 30–40 km (from the top of the basement), respectively, in the central OJP. Moreover, a mantle discontinuity was also imaged at the depth of 55–60 km (from the top of the basement) in the central OJP. These boundaries were not imaged outside the OJP, implying that they are characteristic features of the OJP. In addition, receiver function images showed Moho signals at the depth of 20 km in the eastern OJP, where few previous seismic exploration surveys have been conducted. This depth is comparable with that found in the Manihiki and Hikurangi Plateaus that were potentially separated from the OJP. Key Points: We produced receiver function images of crustal and uppermost mantle structure beneath the Ontong Java Plateau (OJP) Multiple seismic discontinuities of the midcrust (10–20‐km depth) and Moho (30–40‐km depth) were imaged in the central OJP A horizontal seismic discontinuity was imaged in the mantle 57–63 km below sea level in the central OJP